Lipid modulation of skeletal muscle mass and function. Issue 2 (8th October 2016) - Lipina, Christopher; Hundal, Harinder S
Abstract: Loss of skeletal muscle mass is a characteristic feature of various pathologies including cancer, diabetes, and obesity, as well as being a general feature of ageing. However, the processes underlying its pathogenesis are not fully understood and may involve multiple factors. Importantly, there is growing evidence which supports a role for fatty acids and their derived lipid intermediates in the regulation of skeletal muscle mass and function. In this review, we discuss evidence pertaining to those pathways which are involved in the reduction, increase and/or preservation of skeletal muscle mass by such lipids under various pathological conditions, and highlight studies investigating how these processes may be influenced by dietary supplementation as well as genetic and/or pharmacological intervention.